Association Between Perceived Stress and Post-Traumatic Stress Disorder Among Medical Staff During the COVID-19 Epidemic in Wuhan City - Mei, Songli; Liang, Leilei; Ren, Hui; Hu, Yueyang; Qin, Zeying; Cao, Ruilin; Li, Chuanen; Fei, Junsong; Yuan, Tongshuang; Meng, Cuicui; Guo, Xinmeng; Lv, Jianping; et al. (Frontiers in Public Health, 2021)
Abstract Background: This study aimed to explore the relationship between perceived stress and post-traumatic stress disorder among medical staffs who worked in Wuhan during the city lockdown resulted from COVID-19 outbreak. Methods: It was conducted in August 2020, which included 516 front-line medical staff age from 21 to 65. The PTSD Checklist-Civilian Version scale, Perceived stress scale, Insomnia Severity Index and Compassion fatigue scale for medical staff were used. Results: The results indicated that 10.5% of medical staffs were found to have PTSD symptoms. And the effect of perceived stress on post-traumatic stress disorder was mediated by insomnia severity. In addition, compassion fatigue moderated the association between perceived stress and post-traumatic stress disorder. Conclusion: This study helped to elucidate the mechanisms underlying the association between perceived stress and post-traumatic stress disorder. It also emphasized the importance of long-term monitoring of the mental health status of medical staffs who supported Wuhan, and advised the relevant medical and health departments to take active interventions and preventive measures for those unsung heroes who put their lives on the line during difficult times.